Medical nihilism - Stegenga, Jacob (Oxford University Press, 2018)
This book defends medical nihilism, which is the view that we should have little confidence in the effectiveness of medical interventions. If we consider the frequency of failed medical interventions, the extent of misleading evidence in medical research, the thin theoretical basis of many interventions, and the malleability of empirical methods in medicine, and if we employ our best inductive framework, then our confidence in the effectiveness of medical interventions ought to be low. Part I articulates theoretical and conceptual groundwork, which offers a defense of a hybrid theory of disease, which forms the basis of a novel account of effectiveness, and this is applied to pharmacological science and to issues such as medicalization. Part II critically examines details of medical research. Even the very best methods in medical research, such as randomized trials and meta-analyses, are malleable and suffer from various biases. Methods of measuring the effectiveness of medical interventions systematically overestimate benefits and underestimate harms. Part III summarizes the arguments for medical nihilism and what this position entails for medical research and practice. To evaluate medical nihilism with care, the argument is stated in formal terms. Medical nihilism suggests that medical research must be modified, that clinical practice should be less aggressive in its therapeutic approaches, and that regulatory standards should be enhanced.